2020
DOI: 10.3390/atmos11101030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Indo-Pacific Warm Pool on the Hadley, Walker, and Monsoon Circulations

Abstract: The Indo-Pacific warm pool (IPWP) is enclosed by a 28 °C isotherm and plays a vital role in controlling atmospheric circulations. However, the effects of changes in regional warm pool sea surface temperatures (SSTs) remain unexplored. We divided the IPWP into the Indian and Pacific sectors and distinguished their responses to natural variability and global warming. Furthermore, we examined the impacts of the interannual variability (IAV) in warm pool SST on the tropical Hadley, Walker, and monsoon circulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Variations in the structure of the Walker circulations are closely tied not only to precipitation and ocean temperature patterns [2][3][4][5] but also to fishery stocks through variations in nutrient supply caused by the upwelling of cold water 6 . Recent studies of the Walker circulation over the Indo-Pacific region have conflictingly suggested either a weakening [6][7][8][9][10][11][12][13][14][15][16] or strengthening 1,3,4,[17][18][19][20][21][22][23][24] pattern in response to global warming. Recent findings have also indicated changes in the Walker circulation using various paleo-proxy datasets and model simulations of the past climate [25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…Variations in the structure of the Walker circulations are closely tied not only to precipitation and ocean temperature patterns [2][3][4][5] but also to fishery stocks through variations in nutrient supply caused by the upwelling of cold water 6 . Recent studies of the Walker circulation over the Indo-Pacific region have conflictingly suggested either a weakening [6][7][8][9][10][11][12][13][14][15][16] or strengthening 1,3,4,[17][18][19][20][21][22][23][24] pattern in response to global warming. Recent findings have also indicated changes in the Walker circulation using various paleo-proxy datasets and model simulations of the past climate [25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…For the IPO (and thus PDO) to be reproduced, TEP needs to be coupled with TWP and the broader Pacific (Henley et al, 2017;Zhang et al, 2018;Kim et al, 2020) -TEP cannot do it alone. The close correspondence between observations and the POGA ensemble shown in Figure 1a of Kosaka and Xie (2016) indicates that the model is reproducing regime shifts in close accord with observations.…”
Section: 33mentioning
confidence: 99%
“…Climate model simulations showed that 85% of the IPWP's expansion in the past decades is a result of human influence (Bai et al 2022). The influence of the recent human-caused expansion of the IPWP on climate systems has been widely discussed, for example Hadley circulation, Walker circulation (Brierley et al 2009, Williams and Funk 2011, tropical cyclones (Webster et al 2006, Benestad 2009, East Asian summer monsoon (Kim et al 2020, Yin et al 2020, Jian et al 2022, MJO (Roxy et al 2019, Dasgupta et al 2020, the El Niño-Southern Oscillation (ENSO) (Sun 2003) and precipitation over different regions (Zhou 2014). Besides, expansion of the IPWP will also have important impacts on its ecological environment, such as changing the species composition and improving the productivity of mangroves in Indonesia (Field 1995, Shearman et al 2013, Patrick et al 2016, changing the life cycle of planktic organisms in the IPWP (Patrick 2016), promoting the growth rate and biomass accumulation of phytoplankton (Winder and Sommer 2012) and altering the patterns and predictors of marine biodiversity (Tittensor et al 2010).…”
Section: Introductionmentioning
confidence: 99%